Un corps à soi : la réécriture du blason dans Odes de Sharon Olds - Juliette Bouanani (Sillages Critiques)
Sharon Olds’ body of work has always been tied to physicality: in a 2017 article, John Freeman calls her “America’s Brave Poet of the Body.” In 2016, she published Odes, a collection of poems inspired by Pablo Neruda’s Odes to Common Things, in which the poet sings of artichokes and wine, praising the beauty of daily life and of abstract notions such as love and friendship. Among Sharon Olds’ many Odes, a collection of “body poems” stands out. These poems bring the “blazon” to mind, a French medieval poetic form in which the feminine body is fragmented and mapped, from head to toe. Echoes of Whitman’s “body electric” can be found in the poet’s “blazons” but the poems are not simply praises. They reveal the layered nature of the “feminine body,” a social, political, and cultural notion. Using Camille Froidevaux-Metterie’s reflexions on “embodied” female experience, I will read these poems through the lens of feminist phenomenology, investigating the many facets of Sharon Olds’ rewriting of the male subject / female object dynamic of this poetic form.